Validitas Media E-Magazine pada Materi Barisan dan Deret Kelas XI SMA - Tarihoran, Angel Christina; Izzati, Nur; Fera, Mirta (Jurnal Kiprah, 2022)
In this era of revolution 4.0, where humans are increasingly required to utilize technology, both information, and communication, it is hoped that Human Resources (HR) will greatly influence the development of the world, especially in the field of education. Currently, in the situation of the COVID-19 Pandemic, the government only recommends students to carry out distance learning, namely online. Therefore, educators need to create teaching media that support to facilitate the implementation of Distance Learning at this time. This study aims to develop an E-Magazine Media on the Class XI High School Line and Series Materials. This research is a type of Research and Development research that refers to the ADDIE model with limitations up to the analysis stage, the design stage, and the development stage. The data collection technique used in this research is using a questionnaire. The instrument used for data collection is a validation sheet for media experts and material experts. The data obtained in the study were in the form of qualitative data and then converted into quantitative data using the Method of Summated Ratings (MSR). The results of this study indicate that the developed E-magazine media meets the valid criteria.